Self-Sustaining Treatment for Active Remediation (STAR): Smoldering Combustion for the Treatment of Recalcitrant Compounds - Grant, G. P.; Major, D.; Scholes, G.; Gerhard, J. I.; Pironi, P.; Torero, J. L.; Switzer, C. (Águas Subterrâneas, 2011)
This presentation will provide an overview of the scientific principles behind Self- Sustaining Treatment for Active Remediation (STAR), and summarize the six years of proof-of-concept research that has been successfully conducted to date. In addition, this presentation will provide the design and results of an in situ STAR pilot study at a former cresol manufacturing facility in New Jersey that was designed to test STAR at a large scale and under saturated conditions (i.e., below ground surface and below the water table).